1977
DOI: 10.1021/jm00222a009
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic agents. 2. Structure-activity studies on N-protected vinyl, 1,2-dibromoethyl, and cyanomethyl esters of several amino acids

Abstract: Previously reported work on N-protected activated esters of phenylalanine has been extended to include N-protected vinyl, dibromoethyl, and cyanomethyl esters of several other amino acids. These compounds have been synthesized and evaluated in Ehrlich ascites carcinoma, Walker 256 carcinosarcoma, and and P388 lymphocytic leukemia tests. Among compounds tested were derivatives of tyrosine, tryptophan, glycine, leucine, proline, aspartic acid, glutamic acid, 4-aminobutyric acid, and 6-aminocaproic acid. Compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…These analogs probably are acted on by tissue kinases, esterases, and proteases once they are introduced into the body. Previous studies indicated that an N-benzy1oxycarbonyl-Lphenylalanine ether analog is not active (1). Biotransformation according to Schemes I and I1 would result in the generation of a number of aldehyde derivatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These analogs probably are acted on by tissue kinases, esterases, and proteases once they are introduced into the body. Previous studies indicated that an N-benzy1oxycarbonyl-Lphenylalanine ether analog is not active (1). Biotransformation according to Schemes I and I1 would result in the generation of a number of aldehyde derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Each compound was injected intraperitoneally (1 mg/day; ie., 33.3 mgkg) into CF1 male mice (-30 g). On the 7th day, the mice were sacrificed; the total volumes of ascites fluid and packed cells (ascites-crit) were determined, and the percentage inhibition was calculated (1). Phenylalanine mustard and mercaptopurine were used as positive controls.…”
mentioning
confidence: 99%
“…4, 4'- (1, 4-piperazinediyl) bis (4-oxo-2-butenoic acid) and its derivative ester which have two unique plane structures (-CO-CH=CH-CO-) and are symmetric with respect to piperazine ring. literatures [6][7][8][9][10] reported that this -CO-CH=CH-CO-N-fragment may be responsible for antimitotic and cytostatic properties, so they could be used as a new useful method for treating cancer. However, as yet, there is no effective method for PBBA and its derivative ester to apply in biomedical field.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were extended to other amino acids, e.g. leucine, glycine, glutamic acid, aspartic acid and tyrosine which afforded similar activities (Loeffler et al, 1977b). Recently a series of N-cbz-hydroxyprolylglycinamides and related derivatives were synthesized and tested as anti-fibrotic agents, i.e.…”
Section: Introductionmentioning
confidence: 99%